Changes in the spatial development of flood hazard areas in Poland between 1990 and 2018 in the light of legal conditions. (March 2021) - Borowska-Stefańska, Marta; Kobojek, Sławomir; Kowalski, Michał; Lewicki, Marek; Tomalski, Przemysław; Wiśniewski, Szymon
Highlights: The changes in land use of flood hazard areas between 1990-2018 showed that their development is connected with environmental and legal factors. Periods 1990-2006 and 2006-2018 stand out of the intensity land use and potential physical damage within areas exposed to floods after 1990. In order to lower flood risk, protection measures should not only include technical, but also, or perhaps primarily, non-technical solutions. The statutory restrictions for flood hazard areas in Poland were not entirely effective. Abstract: The study presented herein focuses on determining the relationship between changes in the scale of economic losses between 1990–2018 which occurred in areas of high (10 %) and medium (1%) probability of flood occurrence as well as flood hazard areas due to the destruction of a stopbank, and changes in legislation affecting the spatial development of such areas within the said period. The analysis of changes in the development of flood hazard areas was conducted by means of the Corine Land Cover database. The results of the analysis were later used to evaluate potential economic losses on flood plains, and then spatiotemporal analysis was applied to identify areas with clusters of high and low loss values and the trends regarding their transformations. In consequence, the identification of municipality (Polish: gmina) clusters allowed us to verify the dependence of such transformations on those factors that could impact their intensity. For that purpose, we analysed the coverage of local spatial development plans for individual clusters. On the basis of the conducted studies, we concluded that the implemented legal solutions are not entirely effective, which has also been stated by the legislator. Nevertheless, the introduced legislative changes were beneficial, as the example of Poland shows. The implementation of the Floods Directive has, to a certain degree, decelerated the process of land use and its development in flood hazard areas.